Evalusi Kinerja Hot Standby Router Protocol (HSRP) dan Gateway Load Balancing Protocol (GLBP) untuk Layanan Video Streaming - Ahmad Akmaluddin; Arini Arini; Siti Ummi Masruroh (Cyber Security dan Forensik Digital, 2019)
Realtime (streaming) data communication has become a major requirement for companies and government institutions. Communication that occurs is not only limited to one particular local area but covers other areas so as to form a broad network (WAN). In building network infrastructure, one of the most important things is how networks can deal with failure (failure) on a computer network consists of failure of devices (devices) that affect Quality of Services (QoS). In every internet network design process, a redundant line is always added to complete the main line. So that if the main line is disrupted, data traffic can be transferred to the backup path, this process is called network redundancy. So that if one gateway dies, another gateway will immediately replace the dead gateway. There are two protocols included in the FHRP, namely Hot Standby Routing Protocol (HSRP), and Gateway Load Balancing Protocol (GLBP), these two protocols that can overcome this problem. So from that this study will discuss which protocol between the two protocols has the best performance in overcoming the problem. Methods of data collection with literature studies and literature studies, simulations carried out with 8 stages (problem formulation, conceptual models, input & output data, modeling, simulation, verification & validation, experimentation, and output analysis). The results of this study provide the best QoS value for the delay value is the HSRP ROUTER protocol, and for the value of packet loss is HSRP, and for throughput value is HSRP and the routing protocol that is appropriate for the network for video streaming services is HSRP